Carbon trading across borders: A comparative review of global trading mechanisms - Nithya Priya, M; Velavan, C; Samsai, T; Premavathi, R; Senthilnathan, S (Plant Science Today, 2025)
The intensifying effects of global warming have pushed countries globally to adopt measures to reduce greenhouse gas (GHG) emissions. Collective national and international measures are necessary, as unbridled carbon emissions continue to exacerbate global warming, extreme weather, sea-level rise and to decline agricultural productivity, posing serious threats to food security, economic stability and public health. Developing countries are particularly vulnerable, with estimated annual climate-related changes exceeding USD 1.7 trillion due to their limited adaptive capacity. Addressing these causes, Carbon Trading presents a market-oriented solution, aspiring to mitigate GHGs by facilitating the buying and selling of emission permits. Under the Paris Agreement, a strongly regulated and tailored carbon market tailored to specific conditions can incentivize cost-effective mitigation, encourage green innovation and promote clean energy and net-zero efforts. A lack of a strong carbon market can lead to significant economic losses, with estimates suggesting that the potential reduction in GDP for developing countries could be as high as 2.8 % by 2050. However, significant challenges remain in price stability, carbon leakage avoidance and coordination with wider policy frameworks This review takes up carbon trading systems across six jurisdictions, viz. the European Union, China, New Zealand, Switzerland, South Africa and India, assessing their structure, problems of implementation, economic efficiency and environmental efficacy within the environments of both developing and developed economies. The reviewed literature reveals notable differences in market maturity, sectoral coverage and price management mechanisms, highlighting significant variations in these areas along with specific challenges.